Replacement of fish oil with Schizochytrium-derived monoglycerides enriched in docosahexaenoic acid on the growth performance, lipid composition, and intestinal microbiota of Pacific white shrimp (Litopenaeus vannamei) - Wei Huang; Wei Huang; Yongkang Song; Xiaonan Wang; Daiyan Lin; Tuyan Luo; Kaimin Cheng; Qiaolian Li; Baoyu Tian; Yongbiao Zheng; Yongjin He (Frontiers in Marine Science)
Docosahexaenoic acid (DHA) positively influences growth development, feed efficiency, physiological functions, and DHA accumulation in aquatic organisms. Recent mammalian studies demonstrate that DHA in the form of monoglycerides (MGs) is more conducive to facilitating the uptake and impact of DHA bioavailability than triglyceride (TG)-derived DHA. In this study, Schizochytrium-derived monoglyceride as a novel structured lipid form enriched in DHA-MGs was used to replace the fish oil of Litopenaeus vannamei diet and the effects of different DHA-MG levels on the growth performance, lipid composition of muscle and hepatopancreas, and intestinal microbiota of L. vannamei were investigated. The results showed that the diet with a high level of DHA-MGs distinctly increased the final weight, weight gain rate, and specific growth rate of L. vannamei. No notable variation in the biochemical makeup of shrimp muscle was detected among the four diets. The increase in DHA-MGs effectively facilitated the accumulation of DHA in the muscle and hepatopancreas of L. vannamei. In terms of lipidomics analysis, the addition of DHA-MGs significantly influenced the lipid species composition and DHA distribution in shrimp muscle and hepatopancreas. Additionally, the obtained results revealed that the addition of DHA-MGs improved the contents of diglycerides and triglycerides from the neutral lipid category with DHA and DHA located at specific positions on the glycerol backbone for shrimp muscle. Meanwhile, the lipid species from the glycerophospholipid category in shrimp tissues treated with four diets performed different variations. Besides that, the incorporation of DHA-MGs influenced the levels of microbial phylum and genus and the abundance of potential bacterial phenotypes for shrimp midgut. It was noted that the addition of DHA-MGs significantly decreased the abundance of potentially pathogenic bacteria, manifesting that DHA-MGs could readjust the intestinal microecological balance for intestinal health. In conclusion, the use of Schizochytrium-derived DHA-MGs to replace the fish oil in shrimp diet boosted the accumulation of DHA into tissues, modified the levels of lipid species with DHA and DHA located at specific positions on the glycerol backbone, and improved the intestinal health for the growth performance of L. vannamei.